Less material / more intelligence - Crippa, Davide; Di Prete, Barbara (Italian journal of engineering geology and environment, 2017)
<span data-sheets-value="{"1":2,"2":"“Less material” could be the principle that guides the archetypal action tending towards the essential form, an action of subtraction of the material in search of a stronger, immediate and convincing idea. For example, the words of Auguste Rodin “I choose a block of marble and chop off whatever I don’t need” or the words of Michelangelo Buonarroti “I saw the angel in the marble and carved until I set him free” go in the same direction. This paper will investigate the “diverse sensitivity” that has used design as frame to an essential thought, searching in the use of less material an opportunity for an aesthetic, functional research as well as for an innovative technology. This is a sensitivity that guides us to an ecology of thought. A sensitivity already present in the way of working of master Angelo Mangiarotti (well-known even in Carrara); when designing a marble object, he immediately put in relation the object itself with its belonging to the block of material. That very special ability of Angelo’s was able to give the stone sector and the history of design a masterpiece of rational thought as is the Cono Cielo, a great lesson on how to make the most of a little! A boldly light tension towards the infinite. Today everything (or almost everything) is Ecodesign, or at least should match the topic of sustainability; in this regard at least two different methods can be identified that can be described with case-histories and have been already used by the masters of Italian design. On the one hand, a design start-up - “Recycled stones” – involving a designer to understand how to use stone offcuts coming from traditional production (the family quarry); on the other hand, a designer who reinvents a material made of marble and wool trying to create a new company based on this insight. Two different attitudes sharing the same research on the topic of waste and scrap as a value. For “Recycled stones” the solution comes from “the ability to watch”, to find a new aesthetic of imperfection out of leftover materials (manufactured as little as possible); an old lesson reminding of the attitude of many Italian artists. On the other hand Marco Guazzini takes the simple marble dust (waste of traditional production) and mixes it with boiled wool (also taken from scrap) to create a new material workable like marble or corian, an approach typical of the world of technology and industrial design. Two similar yet different stories to describe two methods for a new “ecology of thought”."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">“Less material” could be the principle that guides the archetypal action tending towards the essential form, an action of subtraction of the material in search of a stronger, immediate and convincing idea. For example, the words of Auguste Rodin “I choose a block of marble and chop off whatever I don’t need” or the words of Michelangelo Buonarroti “I saw the angel in the marble and carved until I set him free” go in the same direction. This paper will investigate the “diverse sensitivity” that has used design as frame to an essential thought, searching in the use of less material an opportunity for an aesthetic, functional research as well as for an innovative technology. This is a sensitivity that guides us to an ecology of thought. A sensitivity already present in the way of working of master Angelo Mangiarotti (well-known even in Carrara); when designing a marble object, he immediately put in relation the object itself with its belonging to the block of material. That very special ability of Angelo’s was able to give the stone sector and the history of design a masterpiece of rational thought as is the Cono Cielo, a great lesson on how to make the most of a little! A boldly light tension towards the infinite. Today everything (or almost everything) is Ecodesign, or at least should match the topic of sustainability; in this regard at least two different methods can be identified that can be described with case-histories and have been already used by the masters of Italian design. On the one hand, a design start-up - “Recycled stones” – involving a designer to understand how to use stone offcuts coming from traditional production (the family quarry); on the other hand, a designer who reinvents a material made of marble and wool trying to create a new company based on this insight. Two different attitudes sharing the same research on the topic of waste and scrap as a value. For “Recycled stones” the solution comes from “the ability to watch”, to find a new aesthetic of imperfection out of leftover materials (manufactured as little as possible); an old lesson reminding of the attitude of many Italian artists. On the other hand Marco Guazzini takes the simple marble dust (waste of traditional production) and mixes it with boiled wool (also taken from scrap) to create a new material workable like marble or corian, an approach typical of the world of technology and industrial design. Two similar yet different stories to describe two methods for a new “ecology of thought”.